Synthesis, characterization and thermal behavior of solid state of some mefenamate of trivalent lanthanides (La, Ce, Pr and Nd) - Campos, Francisco X. [UNESP]; Nascimento, André L. C. S. [UNESP]; Colman, Tiago A. D. [UNESP]; Gálico, Diogo A.; Treu-Filho, Oswaldo [UNESP]; Caires, Flávio J. [UNESP]; Siqueira, Adriano B.; Ionashiro, Massao [UNESP] (Springer Nature, 2016)
Solid-state Ln(Mef)3 compounds, where Ln stands for some trivalent lanthanides (La, Ce, Pr and Nd) and Mef is the mefenamate (C15H14NO 2 -) ligand, were synthesized. The characterization and thermal and spectroscopic study of the compounds were performed using elemental analysis, complexometry, image analysis by field emission gun, simultaneous thermogravimetry and differential scanning calorimetry coupled to Fourier transform infrared spectroscopy, X-ray diffractometry, near-infrared and mid-infrared spectroscopy. All the analyses showed that the compounds were obtained in the anhydrous state. The thermoanalytical results showed that the stability and thermal behavior were markedly influenced by the atmosphere used. Moreover, the curves show that the thermal decomposition takes place in two or three steps, with the formation of lanthanide oxide (La2O3, CeO2, Pr6O11 and Nd2O3), as the final residue. Furthermore, the theoretical and experimental spectroscopic data suggested the possible modes of coordination of the ligand with the metals. The DR spectra provided information about the ligand absorption bands and the f-f transitions of Nd3+ and Pr3+ ions.
Keywords: DFT; Lanthanides; Mefenamate; Spectroscopy; Thermal analysis